PLAN DE MARKETING PARA LA LAVADORA “LAVA EXPRESS" DE LA CIUDAD DE LOJA. - Maldonado Quito, Pablo Santiago (2019)
This present research work called “MARKETING PLAN FOR THE “EXPRESS LAUNDRY” LAUNDRY IN LOJA CITY” has been elaborated with the purpose to contribute to the economic development of the enterprise through the best quality services. It was focused on two important aspects such as bibliographic and field research. In reference to the first aspect, it is based on the theoretical foundations related to definitions, objectives, characteristics, classification and structures of each one of the elements of the marketing plan. The second one refers to the application of 360 surveys to the clients of this laundry and the observation visits to the enterprise. The obtained results of the interviews allowed me to identify positive and negative aspects. Among the positive aspects, I can mention that a big percentage of clients takes this service for at least two years, they prefer the laundry machine, not only for clothes, moreover they wash curtains, blankets and other bed clothes also they prefer the ironing service, etc. They are very satisfied with this type of service because for the punctuality and the quality service. Although I could find some negative aspects, which helped to formulate a new proposal for the enterprise For instance, the proposed marketing plan is directed to the presentation of the product, to improve the quality service, to establish agreements with nearby enterprises, to increase promotions and the application of new media strategies where we can use the best communication technologies.